Community extension program to the persons deprived of liberty in the Philippines - Kilat, Ronnel Victor; Valle, Lislee; Costan, Emily; General, Edralin; Costan, Felix; Batican, Ivy; Olivar, Gladies Mae; Batulan, Denilin; Alcantara, Gerly (Edelweiss Applied Science and Technology, 2025)
Philippine higher education institutions have a social responsibility to implement integrated community extension programs that address issues faced by marginalized groups. These initiatives empower communities through knowledge and technology transfer, workshops, and seminars. One extension program of Cebu Technological University Danao Campus focuses on Persons Deprived of Liberty (PDLs), helping them acquire meaningful skills. This study explores the experiences of PDLs who participated in Cebu Technological University Danao Campus’s extension initiatives, including health services, skills enhancement, livelihood programs, and jail visitation. Using a qualitative approach, the study engaged five purposively selected PDLs through active interviews and relational content analysis to examine their experiences and suggestions. Findings highlight the positive impact of these programs on the PDLs’ mental health, personal development, and sense of purpose. Participants also suggested additional training to further enhance the program’s relevance and sustainability. Based on the PDLs’ experiences, a community extension model was created to meet their specific needs. It includes livelihood and mental health programs to support rehabilitation and prepare them for life after release. This model can be used by other institutions to offer similar programs, demonstrating that education-based initiatives can build hope, teach valuable skills, and support positive change.